Association of endometriosis with human papillomavirus (HPV) infection: a systematic review - Sienko, Anna; Urban, Aleksandra; Urban, Aleksandra; Szwed, Carolyn; Sienko, Jacek (Family Medicine & Primary Care Review, 2023)
Endometriosis is defined as the presence of endometrial tissue outside of the uterine cavity. It is a chronic disease affecting approximately 10% of women. In addition to producing a vast array of symptoms, including chronic pelvic pain and dysmenorrhea, the condition significantly impacts quality of life. Over the past century, several theories have attempted to explain the pathogenesis of this complex disease. Recent studies have investigated the potential role of human papillomavirus (HPV) infection in the development of endometriotic lesions. The objective of this review was to conduct a search of online databases (Embase, Medline and PubMed) for available literature from June 2013 to June 2023 concerning the association between HPV and endometriosis. After screening 110 articles, 23 studies met the eligibility criteria, and 8 were included in the systematic review. Out of the 8 reviewed papers, 3 described a statistically significant correlation between HPV infection and endometriosis. 3 others only demonstrated a higher incidence of HPV infection in patients with confirmed endometriosis. A difference in the dominant type of HPV serotype among patients diagnosed with endometriosis was also observed. Given these results, it is difficult to propose a viral origin of the disease. Further research is necessary to determine the role of HPV infection in the development of endometriosis.